Immunogystochemical (Sd-138 Marker) Results Of Pathomorphological Changes In The Uterus When Drinking Energy Drinks Chronically Under Experimental Conditions (Texas Journal of Medical Science, 2024)
In this study, the experimental method examined the morphological changes that occur in uterine tissue and glands when white non-breeding rats are ingested in chronic energy drinks in an immunogystochemical manner. From micropreparations made from uterine tissue structures isolated from white non-breeding bats, immunogystochemical testing was performed using the CD-138 marker to produce data on the results obtained based on the degree of expression of the same marker